SARCOSPORIDIA OF DOMESTIC ANIMALS OF KUVA DISTRICT OF FERGANA REGION AND THEIR SPECIES COMPOSITION (American Journal of Research in Humanities and Social Sciences, 2022)
Internal organs of domestic animals (cattle, sheep and goats) living in different ecological conditions of Kuva district of Fergana region (neck, muscles, esophagus, tongue, heart, diaphragm, and liver, lungs, kidneys, and spleen).